Distribusi Penyuluh Agama Buddha dan Kepuasan Umat pada Masa Pascapandemi di Kalimantan Utara - Aditya Dhammajaya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the dynamics of Buddhist religious counseling services in North Kalimantan Province in the post-pandemic period, particularly focusing on satisfaction levels and the distribution of counselors across districts. Using a quantitative approach with descriptive and correlational designs, the study involved a population of 9 Buddhist counselors and 3,993 congregants, with 98 selected respondents. Satisfaction levels were measured using the SERVQUAL framework, which evaluates service quality through five key dimensions. Findings show an overall satisfaction score of 3.65 (out of 5), categorized as “satisfied.” The highest rating was in the assurance dimension, reflecting public trust in counselor competence. However, empathy and responsiveness dimensions scored lower, especially in regions with few or no assigned counselors. A Pearson correlation analysis yielded a weak positive relationship (r = 0.214) between counselor-to-congregant ratios and satisfaction scores, emphasizing that equitable distribution is more crucial than sheer numbers. This research underscores the urgent need for needs-based distribution policies and hybrid service strategies that combine digital and in-person modalities. The results offer important policy implications, highlighting that spiritual service equity contributes to social cohesion and emotional well-being, especially in pluralistic and geographically dispersed regions.